Pengaruh pemberian kalsium terhadap perubahan karakter anatomi pelepah bibit kelapa sawit tercekam kekeringan - Novi Yulanda Sari; Eka Tarwaca Susila Putra (Fakultas Pertanian Universitas Majalengka, 2023)
One of the environmental limiting factors on the growth and productivity of oil palm is drought stress. Various studies have shown that besides inhibiting the oil palm’s physiological and biochemical processes, severe drought stress also causes morphological changes in the form of oil palm frond fractures. However, research related to calcium’s role in increasing the oil palm seedling’s resistance exposed to drought stress is still limited. This research was conducted to determine the calcium effect and drought stress on the frond anatomical character changes of oil palm seedlings. The study was conducted using a complete randomized block design consisting of two treatments with three replications. The first treatment is drought stress level: field capacity, moderate, and severe drought stress. The second treatment is calcium dose: 0, 50, 100, and 150%. The results showed that drought stress at moderate and severe levels decreased the length and width of epidermal, hypodermis thickness, phloem, and xylem diameter of oil palm frond seedlings. Supplying Ca at 0.08 g increased the cohesiveness and structural strength of frond tissue by increasing the length and width of epidermal tissue and phloem diameter.